Barnard’s Brachiella sp., Parabrachiella supplicans (Barnard, 1955) and Eubrachiella sublobulata (Barnard, 1955) (Copepoda: Siphonostomatoida: Lernaeopodidae) deposited in the Iziko South African Museum - Lebepe, Modjadji C.; Dippenaar, Susan M. (Zootaxa, 2016)
The family Lernaeopodidae Milne Edwards, is one of the largest families in Siphonostomatoida Thorell, with more than 260 valid species. Brachiella sp., Parabrachiella supplicans (Barnard) and Eubrachiella sublobulata (Barnard) collected from Table Bay by Barnard in 1955 off Liza ramada (Risso), Genypterus capensis (Smith) and Congiopodus torvus (Gronov) respectively, are re-examined. Brachiella sp. is identified as Parabrachiella mugilis (Kabata, Raibaut & Ben Hassine) and is synonymized with Parabrachiella exilis (Shiino) based on the general morphology of the female habitus, the type host and the attachment site on the host. Parabrachiella supplicans is redescribed and synonymized with Parabrachiella genypteri (Capart) also collected off G. capensis from Fort Rock Point, Namibia. Additionally, Eubrachiella sublobulata is redescribed and represents a different geographical range and host record for the genus Eubrachiella as species were previously reported from teleosts of Antarctic waters.